Efek Suplementasi Selenium terhadap Marker Darah Pasca Cedera Kontusio - Daba, Mariel; Goenawan, Hanna; Tarawan, Vita Murniati; Rosdianto, Aziis Mardanarian; Lesmana, Ronny (Faculty of Medicine, Universitas Andalas, 2021)
Selenium is a trace element that has antioxidant properties and is a component of selenoproteins. In certain circumstances, such as injury, selenium supplementation is required to regulate the inflammatory response. Contusion injury increases the inflammatory response to a muscle or tissue that begins with vasodilation, increases blood flow, increases vascular permeability, and leads to edema formation at the site of injury. Objectives: To determine the effect of selenium supplementation on changes in blood markers in rats treated with contusion injury. Methods: Experimental design, using experimental male rats (Rattus norwegius), eight weeks old, weighing 200-220 grams, divided into three groups, namely: The Control group, the contusion group, the contusion + Selenium group. Selenium supplementation was given orally on days 1-3 after injury at a dose of 0.0153 mg into 2% PGA. Examination of markers such as White Blood cells (WBC), lymphocytes, monocytes, and neutrophils was carried out on day three after treatment. Results: This study found that the administration of post-muscular selenium supplementation based on examination of blood markers such as WBC, Lymphocytes, Monocytes was higher in the contusion group and lower in the selenium group. Neutrophils were higher in the contusion and selenium groups. This was not significantly different from the control group. The result of blood marker examination tended to change, but it was not statistically significant. Conclusion: Selenium supplementation in post-contusive injury mice did not provide significant changes in blood markers such as WBC, lymphocytes, monocytes, and neutrophils.Keywords: Â antioxidant, blood marker, contusion, selenium